Allopurinol attenuates acute kidney injury following Bothrops jararaca envenomation. - Pedro Henrique França Gois; Monique Silva Martines; Daniela Ferreira; Rildo Volpini; Daniele Canale; Ceila Malaque; Renato Crajoinas; Adriana Castello Costa Girardi; Maria Heloisa Massola Shimizu; Antonio Carlos Seguro (Public Library of Science (PLoS), 2017)
Snakebites have been recognized as a neglected public health problem in several tropical and subtropical countries. Bothrops snakebites frequently complicate with acute kidney injury (AKI) with relevant morbidity and mortality. To date, the only treatment available for Bothrops envenomation is the intravenous administration of antivenom despite its several limitations. Therefore, the study of novel therapies in Bothrops envenomation is compelling. The aim of this study was to evaluate the protective effect of Allopurinol (Allo) in an experimental model of Bothrops jararaca venom (BJ)-associated AKI. Five groups of Wistar rats were studied: Sham, Allo, BJ, BJ+Allo, BJ+ipAllo. BJ (0.25 mg/kg) was intravenously injected during 40'. Saline at same dose and infusion rate was administered to Sham and Allo groups. Allo and BJ+Allo groups received Allo (300 mg/L) in the drinking water 7 days prior to Saline or BJ infusion respectively. BJ+ipAllo rats received intraperitoneal Allo (25 mg/Kg) 40' after BJ infusion. BJ rats showed markedly reduced glomerular filtration rate (GFR, inulin clearance) associated with intense renal vasoconstriction, hemolysis, hemoglobinuria, reduced glutathione and increased systemic and renal markers of nitro-oxidative stress (Nitrotyrosine). Allo ameliorated GFR, renal blood flow (RBF), renal vascular resistance and arterial lactate levels. In addition, Allo was associated with increased serum glutathione as well as reduced levels of plasma and renal Nitrotyrosine. Our data show that Allo attenuated BJ-associated AKI, reduced oxidative stress, improved renal hemodynamics and organ perfusion. It might represent a novel adjuvant approach for Bothrops envenomation, a new use for an old and widely available drug.